2018
DOI: 10.4103/0366-6999.221273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-term Outcomes in Patients with Premature Triple-vessel Coronary Disease Undergoing Three Different Treatment Strategies

Abstract: Background:Patients with premature triple-vessel disease (PTVD) have a higher risk of recurrent coronary events and repeat revascularization; however, the long-term outcome of coronary artery bypass grafting (CABG), percutaneous coronary intervention (PCI), and medical therapy (MT) alone for PTVD patients is controversial. The aim of this study is to evaluate the long-term outcome of PTVD patients among these three treatment strategies, to find out the most appropriate treatment methods for these patients.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Clinical trial and cohort studies provide suitable information on the effectiveness of treatments. The effectiveness among patients in studies may have differences and similarities [ 14 22 ]. The results of a single study are not sufficient to make a decision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical trial and cohort studies provide suitable information on the effectiveness of treatments. The effectiveness among patients in studies may have differences and similarities [ 14 22 ]. The results of a single study are not sufficient to make a decision.…”
Section: Discussionmentioning
confidence: 99%
“…The age range of this study (20–60 years old) is very close to the PCAD age range. As in most literature works, premature coronary artery disease (PCAD) is defined as the occurrence of an acute myocardial infarction (MI) or a symptomatic myocardial ischemia with an obstructive coronary artery disease (stenosis 70%) before age 55 [ 6 , 14 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percutaneous coronary intervention (PCI) has developed rapidly during the past four decades, which has increasingly become one of the mainstream treatments for coronary atherosclerotic heart disease (CHD) [1][2][3]. Previous studies have shown that revascularization therapy, both PCI and coronary artery bypass graft (CABG), could reduce all-cause mortality and cardiac death among patients with complex high-risk coronary disease in contrast to conventional medication treatments [4,5]. Regarding the preference for the revascularization strategy, numerous studies recommend CABG to patients who are under such complex high-risk coronary conditions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%